Stock market reaction to wrongdoing by business leaders: Empirical study in Vietnam - Loan, Nguyen Thi Thanh; Hung, Dang Ngoc; Van, Vu Thi Thuy; Ha, Hoang Thi Viet (Asian Economic and Financial Review, 2025)
This article presents a comprehensive study that explores the effects of misconduct disclosure by business leaders on the stock prices of companies listed on the Vietnamese stock market. The focus of the research is on cases of corporate misconduct involving leaders who faced prosecution and detention between the years 2012 and 2022. To conduct this study, the authors meticulously gathered data from a variety of reliable media sources, such as Tuoi Tre newspaper, Tien Phong newspaper, and Urban Economic newspaper. Through this research, they identified nine business leaders whose alleged misconduct resulted in legal actions, directly linking them to a total of 24 publicly traded companies on the Vietnamese stock exchange. The findings of the study indicate a significant correlation between the disclosure of misconduct and stock price fluctuations. Specifically, the shares of the relevant companies experienced an abnormal return decrease of 4.5% on the day of the misconduct disclosure. Furthermore, when examining a broader event window ranging from five days before to five days after the announcement (denoted as [-5, +5]), the study recorded a statistically significant reduction in stock prices of 22%. These results highlight the detrimental impact that misconduct by business leaders has on investor confidence and decision-making processes. The study underscores the importance of ethical leadership in maintaining investor trust and the stability of stock markets. It serves as a reminder of how corporate governance and transparency play crucial roles in influencing market dynamics.